The standard anatomical textbook of Islam : the manuscript of Tashrih-i Mansuri in National Library of Medicine -USA - Ziaee, Ali Akbar (2010)
In the 15th century, Anatomy of the body written by Mansur ibn Ilyas contained anatomical illustrations. There are sets of full-page anatomical drawings with mixed Persian-Arabic labeling that illustrate arteries, veins, nerves, bones, muscles and a pregnant woman. No full-page anatomical illustrations of the body are preserved from the Islamic world before those which accompanied the Persian treatise composed by Mansur ibn Ilyas. His illustrated treatise, often called 'Mansur' anatomy', was dedicated to a grandson of Timur (Tamerlane) who ruled the province of fars from 1394 to 1409 (797-811 H). It consists of an introduction followed by 5 chapters on the 5 'systems' of the body. A concluding section on compound organs, such as the heart and brain, and on the formation of the fetus, was illustrated with a diagram showing a pregnant woman. In these research, i focus on this book which has an old manuscript in National Library of Medicine in US.